The idea of a social science and its relation to philosophy - Winch, Peter (Routledge, 2008)
In the fiftieth anniversary of this book's first release, Winch's argument remains as crucial as ever. Originally published in 1958, The Idea of a Social Science and Its Relation to Philosophy was a landmark exploration of the social sciences, written at a time when that field was still young and had not yet joined the Humanities and the Natural Sciences as the third great domain of the Academy.